Evaluating the impact of the upgrades to the facilities at Namibia's largest international airport - Emvula, Aune Nyanyukweni (Research of GSB, 2018)
Infrastructure development is vital and plays a big role in economic development of any state as high and sustainable economic growth requires modern and reliable infrastructure. However, due to risks related to time, quality, cost and scope, infrastructure investments do not always result in benefits that fuel economic development. The study identified two problem areas: (a) the current airport infrastructure is not sufficient to support aviation expansion as well as other modes of transport as per the NDP4; and (b) the airport was faced with a downgrade in its firefighting category during July 2014 following the DCA site audit findings. This study was conducted to establish whether funds that were invested for the upgrade and renovation of the HKIA facilities in the 2013/2014 year resulted in improvements that fuel economic and social development in Namibia; and to explore whether participants in the study perceive the investment as money well spent. The study uses a mix of qualitative and quantitative methodologies in order to allow the cohort of insight into the subject matter. Themes and propositions materialised from the data that back the following conclusions: (1) it is the participants' perception that the project enhanced the airport infrastructure and complemented other core elements which could be met to grow economic and social development further; (2) there is a close correlation between passengers/aircrafts movements and the investment made to the airport; (3) the upgrades to the airport resulted in its ability to demonstrate firefighting capabilities and its compliance to the ICAO firefighting requirements; (4) the project lacked involvement by the Namibian government who is the sole shareholder of the NAC and a financier of the HKIA project; (5) there is no aviation policy in the country to guide the aviation sector in its activities; and (6) the investment levels at the HKIA are considered too low as the current terminal building area is unable to complement the growing demand at HKIA. Most importantly, HKIA is a gateway for tourists and investors into Namibia, and requires excessive strategic planning and transformation in terms of its infrastructure, in order to carry out this function efficiently and in a sustainable manner. Therefore, there is a need for a funding mechanism that is sustainable to further develop the HKIA and consequently the economy.